Fiscal space and increasing fiscal resilience. - Aizenman, Joshua (Economics working papers.)
The paper compares fiscal cyclicality across regions and countries from 1960 to 2016. It finds that more than half of 170 countries analyzed in seven regions had, in more recent years, limited fiscal space, and that their fiscal policy was either cyclical or procyclical. This was particularly apparent since the 2008 2009 global financial crisis, which was marked by increased procyclical government spending when accounting for net acquisition of nonfinancial assets and capital expenditure. We construct a limited fiscal capacity statistic, measured by public debt average tax revenue ratio and its volatility, which is found to be positively associated with fiscal procyclicality. The cyclicality is asymmetric: on average, a more indebted government (relative to the tax base) spends more in good times and cuts back spending indifferently compared with low debt countries in bad times. Having sovereign wealth funds is also associated with larger countercyclicality. An enduring interest rate rise entails diminished fiscal space−a 10% increase in the public debt tax base ratio is associated with an upper bound of a 5.6% increase in government spending procyclicality.